Literature Study: The Correlation Between Self-Efficacy and Academic Anxiety in College Students - Rachma Kusuma Wardani; Hayyu Nur Larasati; Sherli Sasmita; Erlina Dwi Agustia (International Conference on Psychology and Education (ICPE), 2023)
This study aims to determine the relationship between self-efficacy and academic anxiety in college students. The method used in this research is a literature study. The data collection technique involves collecting several studies to answer the analysis technique used, which is the content analysis technique. To maintain the integrity of the assessment and prevent incorrect information in the data analysis, bibliography checks and literature re-reading were conducted. The results of this study as well as the conclusion are that there is a strong negative relationship between self-efficacy and academic anxiety in students. The higher the self-efficacy, the lower the academic anxiety of students. The conclusion of this research is evident from several other research results that have been carried out previously that are relevant to the topic we take.